Pediatric Fistula Initiative: Reducing Bloodstream Infections in an Outpatient Pediatric Hemodialysis Center. (10th June 2014) - Chotikanatis, Kobkul; Suman, Nisha; Bäcker, Martin; Paudyal, Bandana; Schoeneman, Morris; Kohlhoff, Stephan; Hammerschlag, Margaret R.
Abstract : Bloodstream infection is a major contributor to morbidity and mortality in children on hemodialysis (HD). From January 2009 through April 2011, the incidence of access-related bloodstream infections (ARBs) in pediatric patients on HD at our hospital was 3.45/1000 patient days. Almost all of these children were receiving HD via central line catheters, and none were receiving HD via arteriovenous fistulas (AVFs). In an effort to reduce the rate of infection in children receiving HD at our institution, we introduced the Pediatric Fistula Initiative, a program to increase creation and use of AVFs in children. Thirty-three children on HD were observed, 9 of whom received AVFs during the study period. The incidence of ARBs decreased to 1.30/1000 patient days (P < .001) during the 24-month intervention period from May 2011 through May 2013.